A clinician's guide to gender-affirming care : working with transgender and gender-nonconforming clients : a comprehensive resource for mental health professionals, educators & students - Chang, Sand C.; Singh, Anneliese A.; dickey, lore m., 1961- (Context Press, 2018)
"Transgender and gender nonconforming (TNGC) clients have complex mental health concerns, and are more likely than ever to seek out treatment. Written by a team of psychologists and TNGC specialists, this comprehensive resource outlines the latest research and recommendations to provide clinicians with the requisite knowledge, skills, and awareness to treat these clients with competent and affirming care."--Provided by publisher.